Financial Ratio Analysis to Predict The Potential of The Company’s Financial Distress With Altman Z-Score Method at PT Bali Kulina Utama - N L Erawati Utami; I M Sudana; L Mei Wahyuni (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Identification of potential financial distress in a company is an important step in predicting the company’s financial health condition. Financial distress conditions can occur before the company goes bankrupt which is marked by a decline in company finances. To deal with these conditions, the company is expected to be able to prepare a strategy to anticipate the occurrence of bankruptcy by analyzing financial ratios. This study aims to calculate, analyze, and classify the potential of financial distress at PT Bali Kulina Utama through financial ratios with the prediction model used is Altman Z-Score Modification method. Primary and secondary data obtained through interviews and documentation data collection techniques. The data analysis technique is descriptive qualitative by calculating each financial ratio that contained in the Altman Z-Score Modification model and calculating the Z-Score Modification equation to predict financial distress position. Based on the results, it can be concluded that the potential of financial distress at PT Bali Kulina Utama in 2018-2020 is in a non financial distress condition, because the Z-Score Modification equation value is in Z”-Score > 2,6.